Effects of Oral Inflammatory Diseases and Oral Hygiene on Atrial Fibrillation: A Systematic Review - Zhanxin Zhang; Fei Chen; Xueying Gao; Bing Xiao; Fan Liu; Jingchao Lu (International Journal of Clinical Practice)
Objective. Research evidence suggests a link between periodontitis (PD) and atrial fibrillation, but the nature of this link is unclear. This study aimed to systematically review and evaluate the association between PD, other oral diseases, and atrial fibrillation and the role of oral hygiene in preventing atrial fibrillation. Methods. We searched the Medline, Embase, Cochrane Library, and Web of Science databases for the clinical study of oral health and atrial fibrillation from inception to November 2022. Oral health conditions included PD and other oral inflammatory diseases, regular oral hygiene, and tooth brushing. The primary outcomes were the risk of new-onset atrial fibrillation in patients with oral disease, the effect of regular oral care on preventing atrial fibrillation, the effect of frequent tooth brushing on preventing atrial fibrillation, and the incidence of atrial fibrillation in PD patients. Results. Eight clinical trials with a total of 4,328,355 patients were included. The result of the research showed that PD and other impaired oral health may be associated with new-onset atrial fibrillation, and its severity was dose-responsive to the risk of atrial fibrillation. The incidence of atrial fibrillation in patients with severe PD was about 16.3%. Moreover, PD may increase the risk of long-term arrhythmia in patients with atrial fibrillation. Regular oral care and frequent tooth brushing can reduce the incidence of atrial fibrillation. Conclusion. Regular and moderate oral hygiene, frequent tooth brushing, and prevention of PD and other oral inflammatory diseases could reduce the occurrence of atrial fibrillation. It is recommended to strengthen the popularization of oral health knowledge in the publicity related to atrial fibrillation.